Capitalism, Climate, and Commitment: A Critical Discourse Analysis of Indonesia’s Green Economy Agenda - Seviatri Yunilasari (fakultas ilmu budaya, 2025)
This research critically examines Indonesia’s green economy agenda through the lens of discourse, focusing on the speech delivered by Hashim Djojohadikusumo at the Opening Ceremony of the Indonesia Pavilion at COP29. Using Norman Fairclough’s Critical Discourse Analysis (CDA) model— comprising textual, discursive, and sociocultural dimensions—alongside John Searle’s Speech Act Theory and Jason W. Moore’s Capitalocene framework, the study investigates how environmental commitments are represented, legitimized, and politicized in elite-level state communication. The textual analysis reveals a dominance of commissive and assertive speech acts, reflecting a strategic projection of commitment and credibility, often framed through vague or euphemistic language. The discursive practice analysis highlights the use of intertextual references (e.g., global treaties, crises, scientific authority) to construct legitimacy while balancing international expectations and domestic interests. The speech performs a dual narrative—both aligning with global climate norms and defending sovereignty-driven development agendas. At the sociocultural level, the research employs Fairclough’s Four-Stage Dialectical-Relational Approach and Moore’s Capitalocene critique to uncover deeper ideological functions of the discourse. The findings show that the speech reinforces capitalist ecological governance by presenting climate action as compatible with extractive development and market-based solutions, while avoiding structural critique. The study identifies a clear shift from technocratic environmental governance toward elite-driven, personalized diplomacy, signaling what may be described as the death of technocratism in favor of oligarchic populism. Overall, the research reveals that Indonesia’s green economy discourse, as performed at COP29, serves more as a tool of symbolic statecraft and international image management than as a platform for transformative ecological governance.
Capitalism, Climate, and Commitment: A Critical Discourse Analysis of Indonesia’s Green Economy Agenda
Reupload file repository 4 februari 2026_agus/feren
Keywords: Green Economy; Commitment